Studi Analisis Deskriptif Partisipasi Masyarakat dalam Perencanaan Pembangunan Infrastruktur Transportasi di Kecamatan Pedurungan Tahun 2013 - Marcelinus Mario Surya Utama; Edi Santoso; Sulistiyowati . (Journal of Politic and Government Studies, 2014)
ABSTRACTStudy of Descriptive Analysis of Society Participation in Planning Development Transportation Infrastructure at Pedurungan District, Semarang 2013This research has aims to : 1) desribe dan analyze succesfull stage of Semarang City Government in accomodating social needs or social aspiration in Pedurungan District, Semarang City supposed to be the participate planning development; 2) describe and analyze synchronization of social proposal with realization2construction of transportation infrastructure.This research belongs to qualitative research aiming to describe in detail and deeply about society participation in development planning in Pedurungan District, Semarang City with some sample of area such as Plamongansari, Pedurungan Kidul, Tlogomulyo and Muktiharjokidul. Data collecting technique used in this research was structured interview and observation also document analyze. Data analysis consisting of data reduction, data display and data verification and conclusion drawing.From the research result, it can be concluded that :1. Eventhough society attendance in some sampling area in high level but the society that being active still in low level;2. The consistency level between planning, budgeting, realitating also synnchronize between bottom up planning and top down planning not yet worked well.3. Management transfer to third partnership that pointed by District SKPD makes a lot of society felt upset with the result because they not involved by government and just could be a supervisor.Therefore, it needs an optimization from government in participate development planning socialication to work well, an accomplishment in participative development planning, and an management transfer to society again.Keywords : Society Participation, Planning Development, Transportation Infrastructure.